2015
DOI: 10.1016/j.algal.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable microalgal biomass production by phycoremediation of a synthetic wastewater: A kinetic study

Abstract: 26Microalgae are considered as one of the most promising sources of biomass for energy 27 production. However, bioenergy production by microalgal culture is still not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 58 publications
4
25
2
Order By: Relevance
“…This trend has already been reported by several authors [37,40,41] and it was also demonstrated in this study, as can be seen in Figure 2 (no adaptation phase was observed). Total N–NH 4 + removal was achieved in assay I, pairing with considerable N–NO 3 − removal efficiencies of about 21%–27%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This trend has already been reported by several authors [37,40,41] and it was also demonstrated in this study, as can be seen in Figure 2 (no adaptation phase was observed). Total N–NH 4 + removal was achieved in assay I, pairing with considerable N–NO 3 − removal efficiencies of about 21%–27%.…”
Section: Discussionsupporting
confidence: 92%
“…In the specific case of assays I and II, average biomass productivities are situated amongst the array of values reported by Silva, et al [37] when using a synthetic wastewater as growth medium. On the other hand, specific growth rates (0.028–0.13 day −1 ) were globally low when compared to typical values reported in the literature of 0.11 and 1.37 day −1 [38,39].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These results also suggested the luxury uptake of phosphorus happened for SDEC-17 in wastewater, as they contained a percentage of phosphorus >1% which indicated normal metabolism [38]. The results agreed with the finding by Silva et al [37] that the removal mechanism of luxury absorption may be more important in media with lower N/P molar ratio like CW, in which higher phosphorus mass concentrations were achieved.…”
supporting
confidence: 94%
“…The ratios between phosphorus and nitrogen removal rate were about or less 1 of in three media, which was in consistent with the data reported by Elrifi and Turpin [34] and Mennaa et al [35], although P requirement for algae is lower than N requirement. These phenomena also indicated a luxury uptake of phosphorus, that has occurred in many algae species, like Chlorella vulgaris and Pseudokirchneriella subcapitata [37], Scenedesmus sp. [31], S. subsalsa [9], mixed microalgae culture [36,38], and so on.…”
Section: Nutrients Utilization Of Monoraphidium Sp Sdec-17mentioning
confidence: 96%